Analisis Blibiometrik: STEAM Dalam Pembelajaran Matematika Berbasis VOS Viewers - Syairah, Anisa; Zulfah; Astuti (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
STEAM can be formed in several ways, one of which is through the process of learning mathematics. The purpose of the blibiometric analysis is to see the development of research trends related to STEAM in mathematics learning based on VOS Viewers. The data collection technique is by searching using Google Scholar using the keyword STEAM in learning mathematics based on 2010 to 2023, there are 1000 articles or journals. Visualization in analysis on vov viewers can be seen in the form of network visualization, overlay visualization and density visualization. Network visualization maps are used to see linkages and research theme clusters related to keywords. Ovelay Visualization is used to identify the year in which the related research theme was carried out. Meanwhile, density visualization is used to analyze research themes that are already saturated and are still rarely researched